Three interval thixotropy test (3ITT) in food applications: A novel technique to determine structural regeneration of mayonnaise under different shear conditions - Toker, Omer Said; Karasu, Salih; Yilmaz, Mustafa Tahsin; Karaman, Safa (ELSEVIER SCIENCE BV, 2015)
In this study, three interval thixotropy test (3ITT) technique was firstly used to determine the effect of instant shear stress or shear rate along with different shear time and temperature values on the deformation and regeneration ability of a food material with respect to applied force during handling, processing, transportation etc. This test technique should be very important in food industry in terms of products like mayonnaise. 3ITT could be used for this aim in order to determine structural deformation and regeneration of food materials. In the present study, mayonnaise was instantly deformed with high levels of shear stress (5, 75, 150 and 200 Pa) or shear rate (100, 500 and 1000 s(-1)) for different time periods (20,40 and 60 s) at different temperature levels (10,25 and 40 degrees C). 3ITT results demonstrated that all shear rate/stress levels at different temperatures and shear times resulted in a remarkable deformation in mayonnaise samples, as revealed by increasing deformation percentage (D-r) values. This increase was also the case in values of time required for the recovery (R-time) values; however, under the highest shear conditions (1000 s(-1) or 200 Pa), no regeneration was observed. Shear rate deformation resulted in higher Dr values than did shear stress deformation, indicating that deformation by shear rate was higher than that by shear stress. As a result, 3ITT was an effective test to apply instant shear stress/shear rate deformation on mayonnaise and collect data on deformation and structural regeneration kinetics, which suggests an effective tool to simulate and analyze effects of real pumping and instant stirring processes during production and handling steps of food materials. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Three interval thixotropy test (3ITT); Mayonnaise; Shear rate/shear stress deformation; Structural regeneration; RHEOLOGICAL CHARACTERIZATION; EGG-YOLK; PROCESSING APPLICATIONS; VISCOELASTIC PROPERTIES; SENSORY PROPERTIES; FLOW BEHAVIOR; STABILITY; TEMPERATURE; EMULSIONS; STARCH; Food Science & Technology